ANALISIS DISIPLIN DAN BUDAYA KERJA PEGAWAI PADA KANTOR CABANG DINAS WILAYAH 5 DINAS PENDIDIKAN PROVINSI LAMPUNG - Ardansyah Ardansyah; Hepiana Patmarina (Jurnal Manajemen dan Bisnis (JMB), 2021)
Abstract Discipline factor plays a very important role in the implementation of employee work. Discipline enforcement itself affects the behavior of each employee. An employee who has a high level of discipline will continue to work well even without being supervised by superiors. A disciplined employee will not steal work time to do other things that have nothing to do with work. Likewise, employees who have discipline will obey the existing regulations in the work environment with high awareness without any sense of coercion. The research method used in this study is a qualitative research method using a soft system methodology approach. Soft system methodology is a research process which in its implementation uses a systems thinking approach. The results of the research are that the employee discipline is not yet optimal, such as violations of the provisions of working hours, the low sense of devotion, awareness and responsibility for official duties, the provision of services to the community that is still not optimal, the use of uniforms that are not in place, violations of disciplinary regulations The current work culture has not shown anything positive in improving employee performance, such as: Lack of communication between employees with superiors and fellow coworkers, there are still employees who are impolite towards fellow employees and superiors, Lack of leadership role in providing encouragement and employee motivation, the implementation of the organization's vision and mission has not been maximized. The recommendation is that the researcher hopes that the research results can be useful for researchers to add scientific insight to researchers regarding human resource management related to the application of discipline and an ideal work culture to improve employee performance. Then it is expected to be a material for consideration and evaluation for the Branch Office of the Regional 5 Education Office of the Lampung Province in implementing discipline and an ideal work culture for its employees by carrying out a series of appropriate and effective policies and decisions. Keywords: Discipline, Work Culture